2022
DOI: 10.3390/jcm11092359
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoamniotic Shunting before 17 + 0 Weeks in Fetuses with Lower Urinary Tract Obstruction (LUTO): Comparison of Somatex vs. Harrison Shunt Systems

Abstract: (1) Background: The aim of this study was to compare perinatal outcomes and complication rates of vesicoamniotic shunting (VAS) before 17 + 0 weeks in isolated LUTO (lower urinary tract obstruction) with the Somatex® intrauterine shunt vs. the Harrison fetal bladder shunt. (2) Methods: This is a retrospective cohort study in two tertiary fetal medicine centers. From 2004–2014, the Harrison fetal bladder shunt was used, and from late 2014–2017, the Somatex shunt. Obstetrics and pediatric charts were reviewed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The benefits of VAS are still controversially discussed; although it has been associated with improved neonatal survival, it failed to significantly reduce the incidence of ESRF in affected children 22 . Recent studies, however, suggest that renal function might be salvaged when the earlier VAS is performed 23 . To what extent VAS might or might not be beneficial in cases of PUV and urinoma formation already taken place could be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of VAS are still controversially discussed; although it has been associated with improved neonatal survival, it failed to significantly reduce the incidence of ESRF in affected children 22 . Recent studies, however, suggest that renal function might be salvaged when the earlier VAS is performed 23 . To what extent VAS might or might not be beneficial in cases of PUV and urinoma formation already taken place could be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recent studies, however, suggest that renal function might be salvaged when the earlier VAS is performed. 23 To what extent VAS might or might not be beneficial in cases of PUV and urinoma formation already taken place could be the subject of future studies. Other prenatal interventions in PUV with urinoma include urinoma drainage, shunting, and PAS in the presence of urinary ascites.…”
Section: Urinoma and Lower Urinary Tract Obstructionmentioning
confidence: 99%
“…As postnatal therapy of megacystis is frequently too late to rescue kidney and respiratory function, several antenatal treatment options have been developed to enable continuous urinary drainage of megacystis into the amniotic cavity, including serial vesicocentesis [ 9 11 ], vesico-amniotic shunting (VAS) [ 12 26 ] or cystoscopic laser valve ablation [ 21 , 27 , 28 ]. All previously published series on antenatal interventions including our own previous studies [ 20 , 24 , 25 ] showed an increase in perinatal survival with the best renal and respiratory outcome after VAS. Indeed, data on intervention-related complications, intrauterine demise, preterm rupture of membrane and preterm delivery varied considerably between the published series, as the numbers of treated fetuses were small and VAS was performed by different operators in different centers at varying gestational ages with different shunt systems.…”
Section: Introductionmentioning
confidence: 86%
“…or I.G.) using a technique as previously described by Strizek et al [ 24 , 25 ]. Genetic testing was offered to all patients, but was not mandatory prior to intrauterine intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation